Prediction of the Next Solar Cycle and Solar Maximum Based on Machine Learning - Xiang, Xuanyi; Zhang, Xinyue; Huang, Qingyi; Liu, Jingyi (Transactions on Computer Science and Intelligent Systems Research, 2024)
The intensity of solar activity varies with the solar cycle of about 11 years, reaching a peak during the solar maximum. Solar activity can affect space weather in ionospheric states and conditions related to shortwave radio propagation or satellite communications, which brings challenges to space exploration, communications, and weather forecasting. Therefore, accurate prediction of the start time and duration of the solar maximum becomes pivotal. In order to solve this problem, this research first applies the K Nearest Neighbors classification algorithm to predict that the beginning of the next solar cycle will be around June 2030 until about July 2040. Then, by establishing the Extreme Gradient Boosting model, this study forecasts that the solar maximum in the next solar cycle will start in August 2034 and last for 8 months. With this accurate prediction of the next solar maximum, aerospace, communications, meteorology, and other industries can reduce the interference of solar activities.